Sustainable Palm Oil Investment Climate in Indonesia: Foreign and Domestic Promotion by the Local Government - Nina Yuslaini; Andriyus Andriyus; Doris Febriyanti; Agung Wicaksono (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2024)
This paper focuses on foreign and domestic palm oil investment promotion strategies in Dumai, Indonesia, to assess the sustainable development investment climate. Exploratory qualitative research is conducted with a case study to examine the foreign and domestic oil palm investment climate. The researchers employed NVivo 12 Plus software and the Biblioshiny application to collect, analyse and visualise bibliometric data. The research indicates that the Dumai government has pursued a strategy to stabilise the foreign and domestic palm oil investment climate by conducting promotions abroad and domestically. The conclusions show that the oil palm investment climate has been unable to positively contribute to economic, social and environmental growth in sustainable development in Dumai. Positive impacts of oil palm investment include offering livelihoods, creating new jobs and increasing local revenue. This research aids the government of Dumai in improving the global palm oil sustainable development investment climate.